LTRs activated by Epstein-Barr virus–induced transformation of B cells alter the transcriptome - Leung, Amy; Trac, Candi; Kato, Hiroyuki; Costello, Kevin R.; Chen, Zhaoxia; Natarajan, Rama; Schones, Dustin E. (Genome Research, 2018)
Endogenous retroviruses (ERVs) are ancient viral elements that have accumulated in the genome through retrotransposition events. Although they have lost their ability to transpose, many of the long terminal repeats (LTRs) that originally flanked full-length ERVs maintain the ability to regulate transcription. While these elements are typically repressed in somatic cells, they can function as transcriptional enhancers and promoters when this repression is lost. Epstein-Barr virus (EBV), which transforms primary B cells into continuously proliferating cells, is a tumor virus associated with lymphomas. We report here that transformation of primary B cells by EBV leads to genome-wide activation of LTR enhancers and promoters. The activation of LTRs coincides with local DNA hypomethylation and binding by transcription factors such as RUNX3, EBF1, and EBNA2. The set of activated LTRs is unique to transformed B cells compared with other cell lines known to have activated LTRs. Furthermore, we found that LTR activation impacts the B cell transcriptome by up-regulating transcripts driven by cryptic LTR promoters. These transcripts include genes important to oncogenesis of Hodgkin lymphoma and other cancers, such as HUWE1/HECTH9. These data suggest that the activation of LTRs by EBV-induced transformation is important to the pathology of EBV-associated cancers. Altogether, our results indicate that EBV-induced transformation of B cells alters endogenous retroviral element activity, thereby impacting host gene regulatory networks and oncogenic potential.
10.1101/gr.233585.117